2022
DOI: 10.3389/fcell.2022.1038358
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in placental insufficiency: What have we learned over time?

Abstract: Genetic variation shapes placental development and function, which has long been known to impact fetal growth and pregnancy outcomes such as miscarriage or maternal pre-eclampsia. Early epidemiology studies provided evidence of a strong heritable component to these conditions with both maternal and fetal-placental genetic factors contributing. Subsequently, cytogenetic studies of the placenta and the advent of prenatal diagnosis to detect chromosomal abnormalities provided direct evidence of the importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 204 publications
0
3
0
Order By: Relevance
“…The clinical outcome of UPD depends on its origin and the chromosome involved. Some UPD events were reported to be associated with FGR, including paternal UPD6 and UPD15 and maternal UPD 6, UPD 7, UPD11, UPD14, UPD15 and UPD20 [7,8,[19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcome of UPD depends on its origin and the chromosome involved. Some UPD events were reported to be associated with FGR, including paternal UPD6 and UPD15 and maternal UPD 6, UPD 7, UPD11, UPD14, UPD15 and UPD20 [7,8,[19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Among others, chronic hypertension and prior PE are well-known risk factors for PE ( Bartsch et al, 2016 ). Placental, maternal, and paternal genetics also significantly contribute to the pathogenesis of PE ( Williams and Broughton Pipkin, 2011 ; Wang et al, 2022 ). The combination of such genetic and environmental factors plays an important role in the development of PE, which is a two-stage process whereby placental dysfunction leads to maternal onset of disease ( Redman et al, 2014 ); several studies have observed PE-associated molecular and histopathological changes in the human placenta, likely reflecting the observed placental dysfunction ( Leavey et al, 2016 ; Benton et al, 2018 ; Wilson et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among others, chronic hypertension and prior PE are well-known risk factors for PE (Bartsch et al, 2016). Placental, maternal, and paternal genetics also signi cantly contribute to the pathogenesis of PE (Williams and Broughton Pipkin, 2011; Wang et al, 2022). The combination of such genetic and environmental factors plays an important role in the development of PE, which is a two-stage process whereby placental dysfunction leads to maternal onset of disease (Redman et al, 2014); several studies have observed PE-associated molecular and histopathological changes in the human placenta, likely re ecting the observed placental dysfunction (Leavey et al, 2016;Benton et al, 2018;Wilson et al, 2018).…”
mentioning
confidence: 99%